DEVELOPMENT OF ORNAMENTAL CACTUS HORTICULTURE CULTIVATION FOR VILLAGE YOUTH - Joko Prayudha .S (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2020)
Cultivation is one of the planned activities of maintaining biological resources carried out on an area of ??land to take advantage or harvest results. The steps taken in this activity are to provide training to young people on how to cultivate horticultural ornamental cactus plants through four stages: 1) Explain the material about an overview of ornamental cactus plants, which includes the definition of ornamental cactus plants and the benefits of cultivating ornamental cactus plants, 2) Planting ornamental cactus plants, treating and controlling pests, 3) Utilizing ornamental cactus plants as economic value, 4) Evaluating the training that has been carried out and drawing conclusions. This activity was carried out with a very good response from the training participants so that they thought this training could be useful in the future. Participants hope that training activities like this can continue with different themes in order to provide education in the development and utilization of existing resources to help from the economic point of view of the local community.